A trend analysis of animal bite cases attending a Tertiary Care Hospital, Odisha during COVID lockdown - Durga Madhab Satapathy; Nivedita Karmee; Sangeeta Das; Debasish Pandit; Jugal Kishor Bhoi (Wolters Kluwer Medknow Publications, 2021)
A nationwide lockdown was imposed from March 25, 2020, to curb the spread of the COVID-19 pandemic. The study aimed to analyze the trend, pattern of animal bite cases and to quantify the reduction in the incidence of animal bite cases due to diminution of exposure time with animals as a result of lockdown. The interrupted time series method was used to evaluate the effect of lockdown on the incidence of animal bite cases. Right after the lockdown, the mean number of reported animal bite cases decreased significantly (P = 0.04) by 8.3%. Furthermore, the month-to-month change of cases for the postlockdown period was in decreasing trend (ß3 = 0.872) and was significant (P < 0.05). Reduction in the exposure time with street animal surely reduce the incidence in animal bite cases and hence, the Government should take appropriate actions to control the intermixing of street dogs with marginal populations at the village and urban slums level.